2022
DOI: 10.1002/smll.202106614
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Defined Undercoordinated Copper Active Sites over Nitrogen‐Doped Carbon for Aerobic Oxidation of Alcohols

Abstract: Lee et al. reported a series of highly active single-site mesoporous Pd/Al 2 O 3 catalysts for selective aerobic oxidation of allylic alcohols. [9] Grassi et al. described gold nanoparticles enclosed in a polymer matrix for oxidative esterification of cinnamyl alcohol with alkyl alcohols. [10] Lee and co-workers developed a zirconia-supported ruthenium catalyst for efficient aerobic oxidation of alcohols to aldehydes. [11] Li et al. found that metal/oxide supported catalysts, such as FeO/Pt(111) or Cu 2 O/ Ag(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…80 Additionally, compared with NC, the reducing role of Zr in the pyrolysis process increased the specific surface area (614 m 2 g −1 ), pore size (5.8 nm) and pore volume (0.716 cm 3 g −1 ) of Zr/NC (Table S1 †), which could significantly facilitate the exposure of active sites and the diffusion of reaction species, and then contribute to the catalytic process. 81 From the scanning electron microscopy (SEM) images in Fig. 2A and B, it can be seen that ZIF-8 and Zr@ZIF-8 displayed a similar rhombic dodecahedron shape with a smooth surface, further indicating that Zr doping did not affect the main structure of ZIF-8, which was in accordance with the results of XRD and FT-IR in Fig.…”
Section: Catalyst Characterization and Intensive Analysissupporting
confidence: 82%
See 1 more Smart Citation
“…80 Additionally, compared with NC, the reducing role of Zr in the pyrolysis process increased the specific surface area (614 m 2 g −1 ), pore size (5.8 nm) and pore volume (0.716 cm 3 g −1 ) of Zr/NC (Table S1 †), which could significantly facilitate the exposure of active sites and the diffusion of reaction species, and then contribute to the catalytic process. 81 From the scanning electron microscopy (SEM) images in Fig. 2A and B, it can be seen that ZIF-8 and Zr@ZIF-8 displayed a similar rhombic dodecahedron shape with a smooth surface, further indicating that Zr doping did not affect the main structure of ZIF-8, which was in accordance with the results of XRD and FT-IR in Fig.…”
Section: Catalyst Characterization and Intensive Analysissupporting
confidence: 82%
“…80 Additionally, compared with NC, the reducing role of Zr in the pyrolysis process increased the specific surface area (614 m 2 g −1 ), pore size (5.8 nm) and pore volume (0.716 cm 3 g −1 ) of Zr/NC (Table S1†), which could significantly facilitate the exposure of active sites and the diffusion of reaction species, and then contribute to the catalytic process. 81…”
Section: Resultsmentioning
confidence: 99%
“…Li et al prepared a Cu 1 /N-C catalyst for the oxidation of cinnamyl alcohol and found that the superoxide produced aer O 2 activation can be combined with cinnamyl alcohol to produce cinnamaldehyde. 168 The Cu dorbital and O p-orbital for cinnamyl alcohol adsorption on Cu 1 / N-C overlapped near −1.30 eV, which is conducive to the catalytic reaction. In organic oxidation reactions, conversion and selectivity are the key parameters to consider the performance of catalysts.…”
Section: Cu-n-c Sacs For the Selective Oxidation Of Organic Compoundsmentioning
confidence: 98%
“…Recently, non-precious SACs were prepared to selectively catalyze the oxidation of alcohols in the face of high cost and scarcity of precious metals 49,50,112,[119][120][121] . The replacement of noble metal is significantly important in cutting cost in industrial application, which requires intensive research toward non-noble metal based SACs.…”
Section: Oxidation Of Alcoholsmentioning
confidence: 99%
“…The M-dN type was widely studied owing to its relatively simple and uniform active sites while an enormous gap is left in the other two types attributed to their complicated electronic states of active sites, which leads to difficulty in characterization and calculation. The nitride-doped carbon (CN) is extensively selected as supports for M-dN [48][49][50][51][52][53][54] . However, new doped sites like O, P, S, Cl have also been reported [55][56][57][58][59][60][61] .…”
Section: Introductionmentioning
confidence: 99%